2019
DOI: 10.1093/carcin/bgz094
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification of cervical lesions using capture sequencing and machine learning method based on HPV and human integrated genomic profiles

Abstract: From initial human papillomavirus (HPV) infection and precursor stages, the development of cervical cancer takes decades. High-sensitivity HPV DNA testing is currently recommended as primary screening method for cervical cancer, whereas better triage methodologies are encouraged to provide accurate risk management for HPV-positive women. Given that virus-driven genomic variation accumulates during cervical carcinogenesis, we designed a 39 Mb custom capture panel targeting 17 HPV types and 522 mutant genes rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
0
27
1
Order By: Relevance
“…Of the integration sites detected, only eight (23%) were within cellular genes. Previous studies have proposed that integration is a directed process that occurs preferentially in/near genes or other genomic features, such as miRNAs or lncRNAs, 6,13,40,42 but our results show more of a stochastic pattern given the wide range of chromosomes affected and low percentage involving genes. However, the number of events we detected is relatively small, and therefore it is challenging to detect predilections for a specific type of location or chromosomal hotspots.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Of the integration sites detected, only eight (23%) were within cellular genes. Previous studies have proposed that integration is a directed process that occurs preferentially in/near genes or other genomic features, such as miRNAs or lncRNAs, 6,13,40,42 but our results show more of a stochastic pattern given the wide range of chromosomes affected and low percentage involving genes. However, the number of events we detected is relatively small, and therefore it is challenging to detect predilections for a specific type of location or chromosomal hotspots.…”
Section: Discussioncontrasting
confidence: 77%
“…One such process that has been investigated as a potential driver of HPV + HNSCC is the process of viral integration. Viral integration has been well characterized in cervical cancer as a marker of disease progression 40 . Studies in cervical cancer and HNSCC have shown that integration into the genome can have a variety of effects on both the cellular and viral genomes, including large‐scale rearrangements, amplifications, deletions, alterations in gene expression and generation of viral‐cellular fusion transcripts 6‐8,11‐13,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this issue, others have begun to use HPV targeted capture sequencing. 5,[15][16][17][18] This strategy allows for better coverage of integration sites than an untargeted approach like WGS but requires sensitive and accurate viral-human fusion detection bioinformatic tools, of which the field has been lacking. In our lab, we have found the previously available viral integration callers to have a relatively low validation rate and limitations on the structural information surrounding the fusion sites, which impairs mechanistic studies.…”
Section: Polymerase Chain Reaction (Pcr)-based Methods Such As Detecmentioning
confidence: 99%
“…Machine learning, an integral part of computational biology, is being increasingly adopted for analyzing health-care and biomedical data to address some of these challenges. In the last decade, machine learning algorithms have gained popularity in medicine and scientific research [ 35 , 58 , 75 ]. A study conducted by Zhang and co-workers successfully discriminated hepatocellular carcinoma tissues from cirrhosis tissues by establishing a computational model based on machine learning method [75] .…”
Section: Introductionmentioning
confidence: 99%